(untitled) (UNIZIK Journal of Marketing, 2026)
Employee participation is increasingly recognized as an important managerial strategy for improving organizational performance, particularly in manufacturing firms operating in emerging economies. This study examined the relationship between employee participation and organizational performance in Nestlé Nigeria Plc. Specifically, it investigated how different forms of participation influence productivity, employee commitment, and the barriers that hinder effective participation. A correlational survey research design was adopted. Data were collected using a structured questionnaire administered to 346 employees selected through stratified random sampling. The instrument demonstrated good internal consistency with Cronbach’s alpha values above 0.70 across all constructs. Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The findings showed a significant positive relationship between employee participation and organizational performance (r = 0.624, p < 0.001). Employee participation explained 38.9% of the variance in organizational performance (R² = 0.389, F(4,341) = 54.27, p < 0.001). Direct participation was the strongest predictor (β = 0.342), followed by consultative (β = 0.287), delegative (β = 0.206), and indirect participation (β = 0.118). Employee participation also significantly influenced employee commitment (β = 0.451, p < 0.001). Key barriers included inadequate communication channels, limited management commitment, and insufficient training. The study highlights the importance of participative management in enhancing organizational performance. Strengthening direct employee involvement, improving communication systems, and providing management training on participative leadership can help organizations maximize the benefits of employee participation.